Pengaruh Kualitas Produk, Kualitas Pelayanan dan Citra Merek terhadap Kepuasan Pelanggan dan Impikasinya pada Loyalitas Pelanggan Klinik Kecantikan Jakarta Barat - Yohana, Elesia Santa; Tj, Hery Winoto; Wahyoedi, Soegeng (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research involves 125 respondents to identify factors influencing customer satisfaction at Erha beauty clinic. The research findings indicate that both product quality and service quality have a significant impact on customer satisfaction. Product quality, encompassing dimensions such as Perceived Quality, product durability, reliability, product features, and aesthetics, plays a key role in enhancing customer satisfaction. Additionally, good service quality is identified as a crucial factor, with deficiencies in this area considered as customer dissatisfaction. However, brand image is not proven to have a significant impact on customer satisfaction. Furthermore, the study reveals that customer satisfaction positively contributes to customer loyalty, a crucial factor for the sustainable growth of Erha beauty clinic. These findings offer a comprehensive insight into the prioritized factors needed to enhance customer satisfaction and loyalty in the beauty industry. Keywords: Beauty Clinic, Brand Image, Customer Satisfaction, Product Quality, Service Quality